Development of a Triple Gene Cry1Ac-Cry2Ab-EPSPS Construct and Its Expression in Nicotiana benthamiana for Insect Resistance and Herbicide Tolerance in Plants - Naqvi, Rubab Z.; Asif, Muhammad; Saeed, Muhammad; Asad, Shaheen; Khatoon, Asia; Amin, Imran; Mukhtar, Zahid; Bashir, Aftab; Mansoor, Shahid (Frontiers in Plant Science, 2017)
Insect pest complex, cotton leaf curl disease (CLCuD) and weeds pose major threat to crop production worldwide, including Pakistan. To address these problems, in the present study a triple gene construct harboring Cry1Ac, Cry2Ab and EPSPS cassettes has been developed for plant specifically in cotton transformation against lepidopteron insect-pests and weeds. Nicotiana benthamiana (tobacco) was used as a model system for characterization of this triple gene construct. The construct has been assembled in plant expression vector and transformed in N. benthamiana. In six transgenic tobacco lines the integration of Cry1Ac-Cry2Ab-EPSPS in tobacco genome was checked by PCR, while successful protein expression of all the three genes was conﬁrmed through immunostrip assay. Efficacy of Cry1Ac and Cry2Ab was evaluated through insect bioassay using armyworm (Spodoptera littoralis). These transgenic tobacco plants showed significant insect mortality as compared to control plants during insect bioassay. Three out of six tested transgenic lines L3, L5 and L9 exhibited 100 % mortality of armyworm, while three other lines L1, L10, and L7 showed 86, 80 and 40 % mortality, respectively. This construct can readily be used with confidence to transform cotton and other crops for the development of insect resistant and herbicide tolerant transgenic plants. The transgenic crop plants developed using this triple gene construct will provide an excellent germplasm resource for the breeders to improve their efficiency in developing stable homozygous lines as all the three genes being in a single T-DNA border will inherit together.